2015
DOI: 10.1177/2055102915579605
|View full text |Cite
|
Sign up to set email alerts
|

Breast is best: Positive mealtime interactions in breastfeeding mothers from Israel and the United Kingdom

Abstract: We examined mealtime interactions to assess whether they varied according to maternal body mass index, country and mode of feeding in 41 Israeli and UK mother–infant dyads. Feeding behaviours were coded using the Simple Feeding Element Scale. Significantly, more UK mothers breastfed during the filmed meal compared to Israeli mothers. Mealtime interactions did not vary according to maternal body mass index or country. Women who breastfed (as opposed to those who bottle fed or fed solids) provided fewer distract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
(63 reference statements)
1
11
0
Order By: Relevance
“…Interestingly, in an earlier study involving the same cohort of mothers it was found that BF was also associated with a more positive mealtime experience than other types of feeding in 2-6 months infants (Shloim, Rudolf, Feltbower, Mohebati & Hetherington, 2015). These findings reveal behavioural benefits of breastfeeding beyond the well characterised nutrient, flavour and antibody content of milk, suggesting that BF promotes communication between mother and infant; providing a beneficial experience compared with other modes of feeding.…”
Section: Introductionmentioning
confidence: 78%
“…Interestingly, in an earlier study involving the same cohort of mothers it was found that BF was also associated with a more positive mealtime experience than other types of feeding in 2-6 months infants (Shloim, Rudolf, Feltbower, Mohebati & Hetherington, 2015). These findings reveal behavioural benefits of breastfeeding beyond the well characterised nutrient, flavour and antibody content of milk, suggesting that BF promotes communication between mother and infant; providing a beneficial experience compared with other modes of feeding.…”
Section: Introductionmentioning
confidence: 78%
“…Infant feeding is an intimate process that determines not only the content and amount of feeding but how a mother and infant interact during feeding (Shloim et al, 2015). Early feeding experiences predict eating later in life (Nicklaus and Remy, 2013).…”
Section: Health and Homeostasismentioning
confidence: 99%
“…Parents who bottle-feed may not recognize the infant’s signals of hunger or fullness and thus overfeed their infant, potentially reducing the infant’s ability to self-regulate when older (Birch, 2006). Breastfeeding the infant can actively regulate the flow of milk from the breast, controlling the pace of the meal and the sense of fullness (Shloim et al, 2015). Long-term effects of early feeding styles have been observed at 6 years of age such that bottle-fed infants are more likely to be expected to empty their bottles and show lower satiety responsiveness compared to breast-fed infants (Li et al, 2014).…”
Section: Health and Homeostasismentioning
confidence: 99%
“…Breastfeeding mothers may be more sensitive and responsive to the hunger and satiety signals communicated by their infant and demonstrate less controlling feeding practices than formula-feeding mothers. Shloim, Rudolf, Feltbower, Mohebati, and Hetherington (2015) observed mealtime interactions between mothers and infants and found that breastfeeding mothers were more in tune with their infants' signals during feeding. Breastfeeding mothers also provided a more favourable feeding environment and fed their infants more responsively than mothers who fed solids or milk from a bottle (Shloim et al, 2015).…”
mentioning
confidence: 99%